2017
DOI: 10.3389/fmicb.2017.01467
|View full text |Cite
|
Sign up to set email alerts
|

In silico Analyses of Subtype Specific HIV-1 Tat-TAR RNA Interaction Reveals the Structural Determinants for Viral Activity

Abstract: HIV-1 Tat transactivates viral genes through strong interaction with TAR RNA. The stem-loop bulged region of TAR consisting of three nucleotides at the position 23–25 and the loop region consisting of six nucleotides at the position 30–35 are essential for viral transactivation. The arginine motif of Tat (five arginine residues on subtype TatC) is critically important for TAR interaction. Any mutations in this motif could lead to reduce transactivation ability and pathogenesis. Here, we identified structurally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…The analysis of clinical characteristics of individuals from French Guiana revealed a significant trend for higher RNA viral loads among B PANDEMIC -infected relative to B CAR -infected subjects, despite no significant differences in clinical condition or CD4 + T cell counts between groups. Previous studies suggested that viral genetic factors contribute to the heritability and variation of viral load set point ( Bonhoeffer et al, 2015 ; Bertels et al, 2018 ) and may also modulate viral replication ( Ronsard et al, 2017a , b ). Whether differences in viral load here observed between subjects reflect selective advantages for BPANDEMIC strains over B CAR ones cannot be answered by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of clinical characteristics of individuals from French Guiana revealed a significant trend for higher RNA viral loads among B PANDEMIC -infected relative to B CAR -infected subjects, despite no significant differences in clinical condition or CD4 + T cell counts between groups. Previous studies suggested that viral genetic factors contribute to the heritability and variation of viral load set point ( Bonhoeffer et al, 2015 ; Bertels et al, 2018 ) and may also modulate viral replication ( Ronsard et al, 2017a , b ). Whether differences in viral load here observed between subjects reflect selective advantages for BPANDEMIC strains over B CAR ones cannot be answered by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the trans-activating regulatory protein Tat controls gene expression and activates viral transcription by binding at the trans-activating response element TAR (Karn and Stoltzfus, 2012 ). It has been shown that point mutations in Tat may lead to more virulent HIV strains with higher stability and transcription efficiency which aggravate the development of novel antiretroviral drugs (Ronsard et al, 2014 , 2017a ; Ronsard, 2017b ). On the other hand, Tat might be a promising vaccine candidate and has shown potential in the reduction of HIV plasma viremia associated with a reduced immune activation (Gray et al, 2016 ).…”
Section: Modeling Hiv Infectionsmentioning
confidence: 99%
“…The high genetic diversity of this virus has increased the concern for developing countries like India, where it has generated various recombinants such as A/C, A/E, and B/C [138]. Critically, genetic variations in the viral genes like Tat and Vif result in differential viral activities, such as 1. varying levels of Tat interaction with the transactivation response RNA (TAR) element [139] and 2. Vif gene-induced differential APOBEC3 degradation [140], which results in a drastic increase of viral gene expression [141].…”
Section: Role Of Autophagy In Diseasesmentioning
confidence: 99%